Biocompatible PEG Grafting on DLC-coated Nitinol Alloy for Vascular Stents - Shin, Hong-Sub; Park, Kwideok; Kim, Ji Heung; Kim, Jae-Jin; Han, Dong Keun; Moon, Myoung-Woon; Lee, Kwang-Ryeol; Shin, Ji Hoon (SAGE PUBLICATIONS LTD, 2009)
The surfaces of Nitinol (TiNi), a popular metal alloy for arterial stents were thin-coated with diamond-like carbon (DLC) and then grafted with poly(ethylene glycol) (PEG) to increase biocompatibility. The TiNi control, DLC-coated TiNi (TiNi-DLC), and the PEG-grafted TiNi-DLC (TiNi-DLC-PEG) surface characteristics and biocompatibility were evaluated. The hydrophilicity of the TiNi-DLC-PEG significantly increased and the amount of both oxygen and nitrogen on the TiNi-DLC-PEG also increased compared to the TiNi control and TiNi-DLC due to the grafted PEG. The ratio between albumin and fibrinogen was higher on the PEG-grafted surface than the other surfaces when tested with human blood components; the platelet adhesion decreased the most on the TiNi-DLC-PEG surface, indicating improved blood compatibility. For in vivo tests using a rat model, the samples that were implanted for 6 weeks formed fibrous tissue; the tissue layer was much thinner on the PEG-grafted sample than the other two groups. The present results indicate that PEG-grafted TiNi-DLC surface may be effective in enhancing biocompatibility of blood-contacting biomaterials including vascular stents.
Keywords: ENHANCED BLOOD COMPATIBILITY; SELF-ASSEMBLED MONOLAYERS; STAINLESS-STEEL STENTS; NEGATIVE CILIA CONCEPT; POLY(ETHYLENE GLYCOL); PROTEIN ADSORPTION; BIOMEDICAL APPLICATIONS; IN-VIVO; SURFACE; PLASMA